DEVELOPMENT OF THE FOOD SAFETY LABELLING TECHNIQUE FOR APPLIED BUSINESS IN THE VIETNAMESE RETAIL FOOD INDUSTRY - Kim, Eunsung; Mcdonald, Scott (Innovare Journal of Food Sciences, 2018)
Objective: This paper proposed the design of Kim and McDonald food safety labeling circuit for managing and examining the effectiveness system and food safety risk management in the food industry. Purpose: This study sought to examine whether differences exist in the food safety labeling practices across government policies between two major retail markets in Vietnam and whether differences exist in the retailer's own logotypes between two major retail markets in Vietnam. Methods: Photography was used in an observational study conducted among two separate retail market chains, all located in Ho Chi Minh City, Vietnam. The study focused on identifying which fresh vegetable categories were labeled and thus used as cases in this study. In which ways are the applications of the developed Kim and McDonald food safety labeling circuit between two separate retail food markets similar and dissimilar being accounted for? The data were collected from a sample of two photographs. The results were analyzed by illustrating the government policy of Vietnamese Good Agricultural Practices (VietGAP) and the retailer's own logo. Results: Both retail market chains show that the identified labels consist of both government standards and the retailer's own logo. Conclusion: The use of the design of Kim and McDonald food safety labeling circuit contributes toward convincing consumers of the quality of products when applying the standards of VietGAP and its strict implementation to meet food safety standards. The purpose of this study is to evaluate how labelling is managed in Vietnam's retail food industry with a special focus on food in Ho Chi Minh City, Vietnam. Furthermore, This study focuses on the way retailers design and uses their labels to identify produce grown under VietGAP standards as well as to gain the consumer's trust that other retailers may learn from through this research. After a brief introduction and literature review, the methodology section is followed by result and discussion section ending with suggestions for the retail food sector.